Islamic boarding schools and human rights enforcement transmission of cultural values for disabilities - Suwarno Suwarno; Uswatun Chasanah (Indonesian Institute for Counseling, Education and Therapy (IICET), 2021)
The inclusive boarding school model is not only a form of embodiment of education that respects diversity and eliminates discrimination. However, it is more critical as a form of application, essence, and religion, the theological substance that teaches the equality of human rights, tolerance, and respect for others in all aspects of life. This research was conducted to know the inclusive boarding school education model initiated by the founder of An-nur Islamic boarding school, Tengku Drs H. Zainal Abidin. The research method used in this study is a type of qualitative research. Data collection techniques using participant observation, namely by way of researchers mingling with the object of research. The research was conducted at the An-nur Islamic Boarding School, Tingkem Asli Village, Bukit District, Bener Meriah Regency, Aceh. The research was conducted from July 2020 to July 2021. The results of this study are that the pesantren model initiated by the founder is an integrated, inclusive boarding school that was officially established in 2010. Inclusive Integration is a pesantren education model that unites regular (typical) students with ABK students (Children with Special Needs) in one Islamic boarding school environment. with an integrated education model, namely the Integration between the concepts of Islamic boarding school education and entrepreneurship with a learning approach that emphasizes emotional and familial. Through this model, Pesantren An-Nur can transmit cultural values for persons with disabilities through the process of enculturation, socialization, acculturation with a Chinatown style building. Cultural transmission is applied to disability in inclusive boarding schools through vertical transmission, oblique transmission, and horizontal transmission. These three cultural transmissions are carried out in the educational process at Islamic boarding schools for 24 hours through theological understanding and translating at the practical level in the form of self-accustoming, exemplary, formal and informal learning, and life skills activities for students in Islamic boarding schools.